Expansion of outer cortical CUX2 neurons requires adaptations for DNA repair - Wenlong Xia; Laura Morcom; Zhaoyang Xu; I-Ling Lu; Qing Wang; Kimberly K. Hoi; Mingming Wei; Keying Zhu; Gregory Jordan; Xiao-Yan Tang; Julio Gonzalez-Maya; Vanesa S. Mattera; et al. (Nature, 2026)
Abstract During mammalian evolution, excitatory neurons in upper cortical layer 2 and layer 3 (L2/3) have shown a disproportionate expansion compared with other layers 1–4 . Replicative expansion of cortical neural progenitors is associated with considerable oxidative DNA damage. Here we show that activating transcription factor 4 (ATF4) has roles as a critical regulator of the DNA damage response, directly activating components of double-stranded DNA repair, including CIRBP, UBA52 and EBF1. Notably, pan-cortical knockout ( Emx1-Cre; Atf4 fl/fl ) demonstrates that ATF4 is required specifically for the development of upper layer 2/3 neurons, marked by the expression of cut-like homeobox 2 protein, CUX2. ATF4 functions to repair DNA damage and attenuate cell death of embryonic radial glial progenitors in a p53-dependent manner. In particular, we show that cold inducible RNA-binding protein (CIRBP) is a transcriptional target of ATF4 that is required for normal phosphorylation of the key double-strand DNA repair factor ataxia telangiectasia mutated (ATM). These findings establish that ATF4 is an essential regulator of the DNA damage response. They further indicate that there are extraordinary requirements for DNA repair after replicative stress in CUX2 + neurons during mammalian brain development.